2021
DOI: 10.1001/jamaneurol.2021.2480
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality Risk of Newer Antiseizure Medications

Abstract: IMPORTANCE Most antiseizure medications (ASMs) carry a US Food and Drug Administration-mandated class label warning of increased suicidality risk, based on a meta-analysis comparing suicidality between individuals treated with medications vs placebo in randomized clinical trials done before 2008. ASMs approved since then carry this warning although they were not similarly studied.OBJECTIVE To review all placebo-controlled phase 2 and 3 studies of 10 ASMs approved since 2008 to evaluate the risk of suicidality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 58 publications
0
34
0
1
Order By: Relevance
“…However, these results are thought to be meaningful in evaluating the drug‐related effects for exploratory purposes, and it has recently been reported that there is no clear evidence of an increased risk of suicidality with cenobamate. 31 The safety results from this study indicate that cenobamate may become an alternative ASM with reasonable exposure and tolerability profiles in Japanese.…”
Section: Discussionmentioning
confidence: 70%
“…However, these results are thought to be meaningful in evaluating the drug‐related effects for exploratory purposes, and it has recently been reported that there is no clear evidence of an increased risk of suicidality with cenobamate. 31 The safety results from this study indicate that cenobamate may become an alternative ASM with reasonable exposure and tolerability profiles in Japanese.…”
Section: Discussionmentioning
confidence: 70%
“…There is a suspect that all ASMs, as a class and across all ranges of indications, may be associated with a small increment of suicidal thoughts or behaviour 32 even though a more recent analysis failed to confirm this finding. 33 In the open-label CNB study, 16 [34][35][36][37][38] are still not available. Hence, we do not know how many drug-resistant patients with focal epilepsies that achieved seizure freedom over few months in the randomized, double-blind studies will keep on without seizures over the years.…”
Section: Drug Reaction With Eosinophilia and Systemicmentioning
confidence: 99%
“…Is it possible that there is a systematic difference in suicidality effects between the drugs considered in the FDA report 2 and the newer drugs considered in the Klein et al publication? 1 That is unlikely. No excess risks of suicide attempt nor completed suicide were discovered among patients taking ASMs, including many patients taking one of the same 5 newer ASMs, in an analysis of medical records in the United Kingdom (“suicidality” could not be measured from these medical records).…”
mentioning
confidence: 98%
“…Klein and coauthors have reported a metanalysis of suicidality associated with the use of 5 newer antiseizure medications (ASMs) using data from the randomized clinical trials (RCTs), and have concluded that there was no statistical association of any of these drugs with suicidality. 1 They were able to do so with confidence because all clinical trials of ASMs after 2008 were required to measure suicidality specifically and prospectively, usually with the Columbia suicidality risk scale. Many earlier RCTs included no specific measurements of suicidality before or after drug assignment, and suicidality was thus detectable only from open-ended enquiry about side effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation